2017
DOI: 10.1016/j.bmcl.2017.07.045
|View full text |Cite
|
Sign up to set email alerts
|

ATP-competitive, marine derived natural products that target the DEAD box helicase, eIF4A

Abstract: Activation of translation initiation is a common trait of cancer cells. Formation of the heterotrimeric eukaryotic initiation factor F (eIF4F) complex is the rate-limiting step in 5′ m7GpppN cap-dependent translation. This trimeric complex includes the eIF4E cap binding protein, the eIF4G scaffolding protein, and the DEAD box RNA helicase eIF4A. eIF4A is an ATP-dependent helicase and because it is the only enzyme in the eIF4F complex, it has been shown to be a potential therapeutic target for a variety of mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…The compound also showed potent inhibition of helicase activity consistent with its ATPase inhibitory activity with complete inhibition at 100 µM. Thus, this data proved that allolaurienterol is an ATP-competitive molecule most likely binding to the ATP-binding pocket at the interface between the N-terminal and C-terminal domains 38,39 .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The compound also showed potent inhibition of helicase activity consistent with its ATPase inhibitory activity with complete inhibition at 100 µM. Thus, this data proved that allolaurienterol is an ATP-competitive molecule most likely binding to the ATP-binding pocket at the interface between the N-terminal and C-terminal domains 38,39 .…”
Section: Discussionsupporting
confidence: 63%
“…This assumption is based on the fact that laurinterol dimer ( 5 ) (Fig. 13 ) does not show activity (IC 50 > 100 µM), possibly due to the increasement in volume of the molecule, which may limit the capacity to interact with the ATPases nucleotide binding pocket 38 , 39 , 43 . Nevertheless, further studies to evaluate this drug target as well as SARs approaches should be developed in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…There are some compounds that have the characteristic of inhibiting eIF4A: silvestrol [59], hippuristanol [60], elisabatin and allolaurintenol [61], rocaglamide [62], and pateamine A and some of its derivatives [30]. These compounds are emerging as a new antiviral therapeutic strategy whose mechanism of action is the inhibition of eIF4A.…”
Section: The Eif4a Inhibitorsmentioning
confidence: 99%
“…DEAD box RNA helicase eIF4A is an ATP-dependent helicase involved in RNA metabolism. It is a potential therapeutic target for a variety of malignancies [ 84 ]. Tillotson et al [ 84 ] reported that marine-derived natural products such as elisabatin A (No.…”
Section: Molecular Targets Of Marine-derived Anticancer Candidatesmentioning
confidence: 99%